Development and evaluation of an illustrated paediatric leaflet 'Coming to Hospital: a guide to what goes on' - Zoë Fritz; Stephen Farrell; Elisha K R Clark; Sanjana S Sanghavi (BMJ Publishing Group, 2021)
Background A paediatric information leaflet was produced to better prepare patients for time spent in hospital and to improve experience by informing them what to expect.Methods The 'Coming to Hospital' leaflet was designed with input from paediatric research groups, and in collaboration with a children's author and publishing company. A questionnaire to evaluate the leaflet was developed; face validity was established in a pilot. The real-time patient experience of these leaflets was evaluated on paediatric wards in a university hospital.Results The evaluation revealed that a significant majority of children 'really liked' the leaflet and found it helpful. 53 out of 72 of children reported that the leaflet made them feel 'happy' or 'calm', with no children responding that it made them feel 'very worried'. The leaflet was found to be informative, well presented and reassuring. Many parents stated that they wished they had received the leaflet prior to their child's first hospital visit. Suggestions for changes to the leaflet were minimal; it was considered to include all relevant information.Conclusion A leaflet designed by clinical staff, patients and a publishing company was welcomed by paediatric patients and their parents. Patients reported it made them feel calmer. Such a leaflet should be available widely to improve children's experience of coming to hospital. Collaborations between clinicians, academics and publishing companies can produce positive results for the paediatric population.